Use of adult dry human mandibles to study of mandibular foramen from various bony landmarks - Mohammad Amaan; Susmita Saha; Prachi Saffar Aneja; Suresh Kanta Rathee; Puneeta Vohra (Wolters Kluwer Medknow Publications, 2024)
Background: Precise knowledge of the mandibular foramen's location is essential for clinical and surgical procedures, especially the inferior alveolar nerve block. Variability in its position concerning different bony landmarks can significantly impact clinical outcomes. Materials and Methods: This study examined 30 Adult dry human mandibles to determine the mandibular foramen's positions in relation to specific bony landmarks: the occlusal plane, posterior border of the ramus, and lingula. Measurements were obtained using a calibrated digital caliper, and statistical analysis was performed. Results: The study revealed significant variations in the position of the mandibular foramen. In relation to the occlusal plane, the mandibular foramen was found at an average height of approximately 15.2 mm (±2.1 mm). Regarding the posterior border of the ramus, it was situated at an average distance of about 18.5 mm (±3.4 mm). In relation to the lingula, the average distance was approximately 21.8 mm (±4.0 mm). These results underscore the considerable individual differences and anatomical variations in the mandibular foramen's location among the studied specimens. Conclusion: The observed variations in the position of the mandibular foramen emphasize the need for clinicians and surgeons to be cognizant of these differences when performing procedures involving the inferior alveolar nerve block. Understanding these anatomical variations is crucial for enhancing clinical precision, reducing complications, and ensuring optimal outcomes.